решить уравнение: (x^2+6x-4)*(x^2+6x-3)=12

решить уравнение:
(x^2+6x-4)*(x^2+6x-3)=12

  • (х+6х-4)*(х+6х-3)=12

    пусть х+6х=а

    тогда

    (а-4)*(а-3)=12

    раскрываем скобки

    а-3а-4а+12=12

    а-7а=0

    а(а-7)=0

    а=0

    а-7=0

    а=7

    возвращаемся…

    х+6х=0

    х(х+6)=0

    х=0

    х+6=0

    х=-6

    х+6х=7

    х+6х-7=0

    D=36+28=64=8

    х=-6+8/2=1

    х=-6-8/2=-7

    Ответ:х=0,х=1,х=-6,х=-7

  • (x+6x-4)(x+6x-3)=12;

    Введем замену:

    x+6x=y;

    (y-4)(y-3)=12;

    y-7y+12=12;

    y(y-7)=0;

    y=0;

    y=7;

    x+6x=0;

    x(x+6)=0;

    x=0;

    x=-6;

    x+6x=7;

    x+6x-7=0;

    x=-7;

    x=1.

    Ответ: Корни уравнения: x=0; x=-6; x=-7; x=1.